Eine Konjektur zu Lukrez 3, 917 - Ullrich, Heiko (Hyperboreus, 2023)
In Lucr. 3. 917 the paradosis oﬀers the otherwise unattested *torrat* which can be restored to regular torreat by reversing the ancient conjectures and accepting two metrical licenses.